Secondary battery and electronic device

CN122800696APending Publication Date: 2026-09-22NINGDE AMPEREX TECHNOLOGY LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511570589.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-30
Publication Date
2026-09-22

AI Technical Summary

Technical Problem

[0003]然而,Si材料作为一种半导体,Si含量提升后其电导率大幅下降,硅的体积膨胀效应也会加剧,导致Si体系锂离子电池的放电能力和循环性能大幅下降,尤其是在高低温环境下,锂离子电池的放电能力和循环性能下降更加明显

Benefits of technology

[0025]本申请提供了一种二次电池及电子装置,二次电池包括负极极片、正极极片和电解液,负极极片包括负极集流体和设置在负极集流体至少一个表面的负极材料层,负极材料层包括负极活性材料,负极活性材料包括含硅材料,基于负极材料层的质量,硅元素的质量百分含量为W1 %,25≤W1≤70。正极极片包括正极集流体和设置在正极集流体至少一个表面的正极材料层,正极材料层包括钴酸锂,钴酸锂颗粒的粒径为D μm,2≤D≤10。电解液包括含氟化合物,含氟化合物包括氟代碳酸乙烯酯或乙酸2,2-二氟乙酯中的至少一种;基于电解液的质量,含氟化合物的质量百分含量为E %,30≤E≤80。通过调控负极材料层中硅元素的质量百分含量、钴酸锂颗粒的粒径以及电解液中含氟化合物的种类及质量百分含量在本申请范围内,可以在提高二次电池的能量密度的同时,有效改善负极侧成膜质量,进而改善二次电池的高温循环性能和低温倍率放电性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122800696A_ABST
    Figure CN122800696A_ABST
Patent Text Reader

Abstract

The application provides a secondary battery and an electronic device, the secondary battery comprising a negative electrode sheet, a positive electrode sheet and an electrolyte, the negative electrode sheet comprising a negative electrode current collector and a negative electrode material layer, the negative electrode material layer comprising a negative electrode active material, the negative electrode active material comprising a silicon-containing material, the mass percentage of silicon element being W1 %, 25≤W1≤70, based on the mass of the negative electrode material layer; the positive electrode sheet comprising a positive electrode current collector and a positive electrode material layer, the positive electrode material layer comprising lithium cobaltate, the particle size of lithium cobaltate particles being D μm, 2≤D≤10; the electrolyte comprising a fluorine-containing compound, the fluorine-containing compound comprising at least one of fluoroethylene carbonate or 2,2-difluoroethyl acetate; the mass percentage of the fluorine-containing compound being E %, 30≤E≤80, based on the mass of the electrolyte. The secondary battery has high energy density, good high-temperature cycle performance and low-temperature rate discharge performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of electrochemical technology, and in particular to a secondary battery and electronic device. Background Technology

[0002] Lithium-ion batteries, as one of the new energy storage devices, have been widely studied and applied due to their advantages such as high energy density, excellent cycle stability, and environmental friendliness. With product iteration and in-depth research, the demand for improving the volumetric energy density (VED) of lithium-ion batteries is increasing day by day. Accompanying this is the gradual transition of lithium-ion battery anode materials from graphite to low-content Si (the percentage of Si element in the anode material layer is ≤10%) and then to high-content Si (the percentage of Si element in the anode material layer is ≥50%).

[0003] However, as a semiconductor, Si material exhibits a significant decrease in conductivity when its Si content is increased, and the volume expansion effect of silicon is also aggravated, leading to a substantial decrease in the discharge capacity and cycle performance of Si-based lithium-ion batteries. This decrease is particularly pronounced under high and low temperature environments. Summary of the Invention

[0004] The purpose of this application is to provide a secondary battery and electronic device that can improve the energy density of the secondary battery while effectively improving the film quality on the negative electrode side, thereby improving the high-temperature cycle performance and low-temperature rate discharge performance of the secondary battery.

[0005] It should be noted that while this application uses lithium-ion batteries as an example of secondary batteries to explain the invention, the secondary batteries in this application are not limited to lithium-ion batteries. The specific technical solution is as follows:

[0006] The first aspect of this application provides a secondary battery comprising a negative electrode, a positive electrode, and an electrolyte. The negative electrode includes a negative current collector and a negative electrode material layer disposed on at least one surface of the negative current collector. The negative electrode material layer includes a negative electrode active material, which includes a silicon-containing material. Based on the mass of the negative electrode material layer, the mass percentage of silicon is W1%, 25≤W1≤70. The positive electrode includes a positive current collector and a positive electrode material layer disposed on at least one surface of the positive current collector. The positive electrode material layer includes lithium cobalt oxide, and the particle size of the lithium cobalt oxide particles is D μm, 2≤D≤10. The electrolyte includes a fluorinated compound, which includes at least one of fluoroethylene carbonate or 2,2-difluoroethyl acetate. Based on the mass of the electrolyte, the mass percentage of the fluorinated compound is E%, 30≤E≤80. By controlling the silicon content within the scope of this application, the secondary battery exhibits a high energy density. By controlling the particle size of the lithium cobalt oxide particles within the scope of this application, the contact between particles is denser, resulting in a superior conductive network, stronger electronic conduction, and more electrochemical reaction active sites, leading to rapid lithium-ion insertion and extraction. This helps to address the problem of significantly reduced discharge capacity caused by high-Si anodes. The electrolyte contains the fluorinated compounds of this application, and the content of these fluorinated compounds is controlled within the scope of this application, effectively improving the film quality on the anode side while having minimal impact on lithium-ion conduction. This helps to address the problem of poor cycle stability caused by high-Si anodes. Therefore, by controlling the mass percentage of silicon in the anode material layer, the particle size of the lithium cobalt oxide particles in the cathode material layer, and the type and mass percentage of fluorinated compounds in the electrolyte within the scope of this application, these three elements can work synergistically to achieve a balance between high energy density, good high-temperature cycle performance, and good low-temperature rate discharge performance in the secondary battery.

[0007] In some embodiments of this application, 32 ≤ W1 ≤ 58. By adjusting the value of W1 within the above range, a balance can be further achieved between high energy density, good high-temperature cycle performance, and good low-temperature rate discharge performance of the secondary battery.

[0008] In some embodiments of this application, 4≤D≤8. By adjusting the value of D within the above range, a more continuous and dense conductive network can be formed, resulting in stronger electronic conductivity. At the same time, small-diameter lithium cobalt oxide particles have suitable electrochemical reaction active sites, which is beneficial to the insertion and extraction process of lithium ions on the particle surface, thereby further improving the low-temperature rate discharge performance of the secondary battery.

[0009] In some embodiments of this application, the mass percentage of fluoroethylene carbonate is E1% based on the mass of the electrolyte, with 10 ≤ E1 ≤ 30. Adjusting the value of E1 within this range is beneficial for improving the film quality on the negative electrode side, thereby enhancing the high-temperature cycle performance of the secondary battery.

[0010] In some embodiments of this application, 10 ≤ E1 ≤ 20. By adjusting the value of E1 within the above range, it is beneficial to further improve the film formation quality on the negative electrode side, thereby further improving the high-temperature cycle performance of the secondary battery.

[0011] In some embodiments of this application, the mass percentage of 2,2-difluoroethyl acetate is E2%, with 20 ≤ E2 ≤ 50%, based on the mass of the electrolyte. By adjusting the value of E2 within the above range, it is possible not only to appropriately increase the dielectric constant of the electrolyte, enhance its solubility for lithium salts, and reduce its viscosity, thus improving its ion conductivity and consequently enhancing the low-temperature rate discharge performance of the secondary battery; but also to form a dense SEI film with good lithium-ion conductivity, which is beneficial for improving the film quality on the negative electrode side and thus improving the high-temperature cycle performance of the secondary battery.

[0012] In some embodiments of this application, 20 ≤ E2 ≤ 40. By adjusting the value of E2 within the above range, the low-temperature rate discharge performance and high-temperature cycle performance of the secondary battery can be further improved.

[0013] In some embodiments of this application, the silicon-containing material is a silicon-carbon material, and based on the mass of the silicon-carbon material, the mass percentage of silicon element is W2%, with 50 ≤ W2 ≤ 85%. By adjusting the value of W2 within the above range, it is beneficial to utilize the high specific capacity of silicon to improve the energy density of the secondary battery, while also controlling the volume expansion and conductivity of the negative electrode at a reasonable level, reducing the rupture of the SEI film due to drastic volume changes, thereby improving the high-temperature cycle performance and low-temperature rate discharge performance of the secondary battery.

[0014] In some embodiments of this application, the negative electrode active material further includes graphite, and the mass percentage of silicon-containing material is W3% based on the mass of the negative electrode active material, with 50 ≤ W3 ≤ 90%. By adjusting the value of W3 within the above range, the characteristics of silicon-containing material and graphite can be balanced. This allows for both improvements in the energy density of the secondary battery through the use of silicon-containing material and enhancements in the low-temperature rate discharge performance and high-temperature cycle performance of the secondary battery by utilizing the excellent conductivity and structural stability of graphite. Furthermore, it can also reduce costs.

[0015] In some embodiments of this application, the silicon-containing material is a silicon-carbon material, and the particle size Dv50 of the silicon-carbon material satisfies: 4μm≤Dv50≤8μm. By controlling the particle size Dv50 of the silicon-carbon material within the above range, the silicon-carbon material can be more uniformly dispersed in graphite to form a continuous conductive network, which is beneficial to improving the low-temperature rate discharge performance of the secondary battery.

[0016] In some embodiments of this application, the silicon-containing material is a silicon-carbon material, and the particle size Dv99 of the silicon-carbon material satisfies: 16μm≤Dv99≤25μm. By controlling the particle size Dv99 of the silicon-carbon material within the above range, the number of ultra-large particles can be controlled, avoiding excessive volume expansion when large silicon-carbon particles are intercalated with lithium, which is beneficial to improving the high-temperature cycle performance of the secondary battery.

[0017] In some embodiments of this application, the silicon-containing material is a silicon-carbon material, and the particle size Dn10 of the silicon-carbon material satisfies: 0.5μm≤Dn10≤3μm. By controlling the particle size Dn10 of the silicon-carbon material within the above range, the proportion of ultrafine particles can be limited, particle agglomeration can be prevented, and it is beneficial to form a continuous conductive network, thereby improving the low-temperature rate discharge performance of the secondary battery.

[0018] In some embodiments of this application, the silicon-containing material is a silicon-carbon material, and the particle size Dv50 of the silicon-carbon material satisfies: 4μm≤Dv50≤8μm; Dv99 satisfies: 16μm≤Dv99≤25μm. By controlling the particle size Dv50 and Dv99 of the silicon-carbon material within the above ranges, it is beneficial to achieve uniform dispersion of the silicon-carbon material in graphite, and the number of ultra-large particles can be controlled, avoiding excessive volume expansion of large silicon-carbon material during lithium intercalation. This is beneficial to improving the low-temperature rate discharge performance and high-temperature cycle performance of the secondary battery.

[0019] In some embodiments of this application, the silicon-containing material is a silicon-carbon material, and the particle size Dv50 of the silicon-carbon material satisfies: 4μm≤Dv50≤8μm; Dn10 satisfies: 0.5μm≤Dn10≤3μm. By controlling the particle size Dv50 and Dn10 of the silicon-carbon material within the above ranges, not only can the silicon-carbon material be more uniformly dispersed in graphite, but the proportion of ultrafine particles can also be limited, preventing particle agglomeration, which is conducive to the formation of a continuous conductive network, thereby improving the low-temperature rate discharge performance of the secondary battery.

[0020] In some embodiments of this application, the silicon-containing material is a silicon-carbon material, and the particle size Dv99 of the silicon-carbon material satisfies: 16μm≤Dv99≤25μm; Dn10 satisfies: 0.5μm≤Dn10≤3μm. By controlling the particle size Dv99 and Dn10 of the silicon-carbon material within the above ranges, the number of ultra-large particles can be controlled, avoiding excessive volume expansion during lithium intercalation of large silicon-carbon materials, and the proportion of ultra-fine particles can be limited to prevent particle agglomeration, thereby improving the low-temperature rate discharge performance and high-temperature cycle performance of the secondary battery.

[0021] In some embodiments of this application, the silicon-containing material is a silicon-carbon material, and the particle size Dv50 of the silicon-carbon material satisfies: 4μm≤Dv50≤8μm; Dv99 satisfies: 16μm≤Dv99≤25μm; and Dn10 satisfies: 0.5μm≤Dn10≤3μm. By controlling the particle sizes Dv50, Dv99, and Dn10 of the silicon-carbon material within the above ranges, the silicon-carbon material can be uniformly dispersed in graphite to form a continuous conductive network, which is beneficial to improving the low-temperature rate discharge performance of the secondary battery; moreover, it can avoid excessive volume expansion when large silicon-carbon material particles are intercalated with lithium, which is beneficial to improving the high-temperature cycle performance of the secondary battery.

[0022] A second aspect of this application provides an electronic device comprising a secondary battery as described in any of the foregoing embodiments.

[0023] Therefore, the electronic device provided in this application has good performance.

[0024] The beneficial effects of this application are:

[0025] This application provides a secondary battery and an electronic device. The secondary battery includes a negative electrode, a positive electrode, and an electrolyte. The negative electrode includes a negative current collector and a negative electrode material layer disposed on at least one surface of the negative current collector. The negative electrode material layer includes a negative electrode active material, which includes a silicon-containing material. Based on the mass of the negative electrode material layer, the mass percentage of silicon is W1%, and 25≤W1≤70. The positive electrode includes a positive current collector and a positive electrode material layer disposed on at least one surface of the positive current collector. The positive electrode material layer includes lithium cobalt oxide, and the particle size of the lithium cobalt oxide particles is D μm, and 2≤D≤10. The electrolyte includes a fluorinated compound, which includes at least one of fluoroethylene carbonate or 2,2-difluoroethyl acetate. Based on the mass of the electrolyte, the mass percentage of the fluorinated compound is E%, and 30≤E≤80. Within the scope of this application, by controlling the mass percentage of silicon in the negative electrode material layer, the particle size of lithium cobalt oxide particles, and the types and mass percentages of fluorine-containing compounds in the electrolyte, the energy density of the secondary battery can be increased while effectively improving the film quality on the negative electrode side, thereby improving the high-temperature cycle performance and low-temperature rate discharge performance of the secondary battery.

[0026] Of course, implementing any product or method of this application does not necessarily require achieving all of the advantages described above at the same time. Attached Figure Description

[0027] To more clearly illustrate the technical solutions in the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this application. For those skilled in the art, other embodiments can be obtained based on these accompanying drawings.

[0028] Figure 1 This is a cross-sectional SEM image of the positive electrode material layer in Embodiment 1-1 of this application;

[0029] Figure 2 This is a cross-sectional SEM image of the cathode material layer in Comparative Example 3 of this application;

[0030] Figure 3 This is a cross-sectional SEM image of the cold-pressed negative electrode material layer of Embodiment 1-1 of this application;

[0031] Figure 4 This is a cross-sectional SEM image of the negative electrode material layer after 200 cycles at 45°C in Example 1-1 of this application. Detailed Implementation

[0032] The technical solutions of this application will be clearly and completely described below with reference to the embodiments and accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. All other embodiments obtained by those skilled in the art based on this application are within the scope of protection of this application.

[0033] It should be noted that, in the specific embodiments of this application, a lithium-ion battery is used as an example of a secondary battery to explain this application; however, the secondary battery in this application is not limited to lithium-ion batteries. The specific technical solution is as follows:

[0034] The first aspect of this application provides a secondary battery comprising a negative electrode, a positive electrode, and an electrolyte. The negative electrode includes a negative current collector and a negative electrode material layer disposed on at least one surface of the negative current collector. The negative electrode material layer includes a negative electrode active material, which is a silicon-containing material. Based on the mass of the negative electrode material layer, the mass percentage of silicon is W1%, 25≤W1≤70, preferably 32≤W1≤58. The positive electrode includes a positive current collector and a positive electrode material layer disposed on at least one surface of the positive current collector. The positive electrode material layer includes lithium cobalt oxide, and the particle size of the lithium cobalt oxide particles is D μm, 2≤D≤10, preferably 4≤D≤8. The electrolyte includes a fluorinated compound, which includes at least one of fluoroethylene carbonate or 2,2-difluoroethyl acetate. Based on the mass of the electrolyte, the mass percentage of the fluorinated compound is E%, 30≤E≤80. For example, the value of W1 can be 25, 30, 32, 35, 40, 45, 50, 55, 58, 60, 65, 70, or a range of any two values; the value of D can be 2, 4, 6, 8, 10, or a range of any two values; the value of E can be 30, 40, 50, 60, 70, 80, or a range of any two values. The aforementioned "negative electrode material layer disposed on at least one surface of the negative electrode current collector" means that the negative electrode material layer can be disposed on one surface of the negative electrode current collector along its own thickness direction, or on two surfaces of the negative electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of ​​the negative electrode current collector, or a part of the negative electrode current collector; this application has no particular limitation, as long as the purpose of this application can be achieved. The aforementioned "positive electrode material layer disposed on at least one surface of the positive electrode current collector" means that the positive electrode material layer can be disposed on one surface of the positive electrode current collector along its own thickness direction, or on two surfaces of the positive electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of ​​the positive electrode current collector or only a part of the positive electrode current collector. This application has no particular limitation, as long as the purpose of this application can be achieved.

[0035] The inventors discovered that when the silicon content in the negative electrode material layer is too high, for example, greater than 70%, the discharge capacity of the secondary battery decreases more significantly due to silicon's poor electron conductivity. Furthermore, the volume expansion effect of silicon is exacerbated, leading to repeated rupture and regeneration of the SEI film, consuming large amounts of electrolyte and lithium ions, and affecting the low-temperature rate discharge performance and high-temperature cycle performance of the secondary battery. When the silicon content in the negative electrode material layer is too low, for example, less than 25%, it is difficult to improve the energy density of the secondary battery. Within the scope of this application, the silicon content in the negative electrode material layer is relatively high, enabling the secondary battery to have a higher energy density. The inventors further discovered that, on the one hand, when the positive electrode active material is lithium cobalt oxide, and the particle size of the lithium cobalt oxide particles is controlled within the scope of this application, the smaller particle size of the lithium cobalt oxide particles results in denser contact between particles, increasing the contact area and forming a more continuous and dense conductive network. This shortens the electron conduction distance within the positive electrode sheet, reduces conduction resistance, and enhances electron conductivity. Meanwhile, smaller-sized lithium cobalt oxide particles have a larger specific surface area, exposing more electrochemical reaction active sites, which accelerates the insertion and extraction of lithium ions on the particle surface. When the particle size of lithium cobalt oxide is too small, for example, less than 2 μm, the particles are prone to agglomeration, which disrupts the continuous and dense conductive network, increasing the resistance to electron conduction. Furthermore, excessively small particles have too many active sites, exacerbating side reactions with the electrolyte. When the particle size of lithium cobalt oxide is too large, for example, greater than 10 μm, there are more pores between particles, resulting in poor continuity of the conductive network and weakened electron conduction. Moreover, large-sized particles expose fewer active sites, which is detrimental to the insertion and extraction of lithium ions on the particle surface. Therefore, controlling the particle size of lithium cobalt oxide within the range specified in this application is beneficial for solving the problem of a significant decrease in discharge capacity caused by high-Si anodes. However, the lithium cobalt oxide particles within the scope of this application have small particle sizes, leading to more side reactions with the electrolyte at high temperatures. Fluorine-containing compounds can improve the high-temperature stability of the electrolyte itself, reduce the degree of reaction between small-particle-size lithium cobalt oxide and the electrolyte at high temperatures, thereby reducing the damage of side reactions to the CEI film on the surface of lithium cobalt oxide, making the CEI film on the surface of lithium cobalt oxide more stable. When the silicon content in the negative electrode is relatively high, the negative electrode SEI film is unstable at high temperatures, affecting the high-temperature cycle performance of the secondary battery. When the electrolyte includes fluorine-containing compounds, and the types and contents of fluorine-containing compounds are controlled within the scope of this application, during the first charge and discharge process of the secondary battery, due to the strong electronegativity of fluorine atoms, the fluorine-containing compounds will preferentially undergo redox reactions on the negative electrode surface before other components of the electrolyte, forming a high-mechanical-strength and dense solid electrolyte interface (SEI) film. This effectively improves the film quality on the negative electrode side, helps to suppress the volume expansion of the high-Si negative electrode, and makes the SEI film less prone to rupture, thereby reducing the continuous decomposition of the electrolyte and improving the high-temperature cycle performance of the secondary battery.When the content of fluorine-containing compounds is too low, for example, less than 30%, it is difficult to form a uniform and dense SEI film on the negative electrode surface; when the content of fluorine-containing compounds is too high, for example, greater than 80%, the formed SEI film is too thick, which is not conducive to lithium-ion conduction. Therefore, when the electrolyte includes fluorine-containing compounds, and the type and content of fluorine-containing compounds are controlled within the scope of this application, it is beneficial to solve the problem of poor cycle stability caused by high-Si negative electrodes. Thus, by controlling the mass percentage of silicon in the negative electrode material layer, the particle size of lithium cobalt oxide particles in the positive electrode material layer, and the type and mass percentage of fluorine-containing compounds in the electrolyte within the scope of this application, the three can work synergistically to achieve a balance between high energy density, good high-temperature cycle performance, and good low-temperature rate discharge performance of the secondary battery. In this application, the above-mentioned high temperature refers to a temperature greater than or equal to 45°C, and the above-mentioned low temperature refers to a temperature less than or equal to 0°C.

[0036] This application does not impose any particular limitation on the method of controlling the particle size of lithium cobalt oxide particles, as long as the purpose of this application can be achieved. For example, the aforementioned lithium cobalt oxide particles of different sizes can be obtained commercially. For example, the particle size of lithium cobalt oxide particles can be controlled by grinding them. For instance, the particle size of lithium cobalt oxide particles can be controlled by adjusting the grinding time. For example, when other conditions remain unchanged, extending the grinding time reduces the particle size of lithium cobalt oxide particles; or, shortening the grinding time increases the particle size of lithium cobalt oxide particles.

[0037] This application does not impose any particular limitation on the method of controlling the mass percentage of silicon in the negative electrode material layer, as long as the purpose of this application can be achieved. For example, the mass percentage of silicon in the negative electrode material layer can be controlled by controlling the mass percentage of silicon-containing material in the negative electrode active material. For example, the mass percentage of silicon in the negative electrode material layer can be controlled by controlling the mass percentage of silicon in the silicon-containing material. For example, the mass percentage of silicon in the negative electrode material layer can be controlled by controlling the mass percentage of negative electrode active material in the negative electrode material layer.

[0038] In some embodiments of this application, the mass percentage of fluoroethylene carbonate is E1% based on the mass of the electrolyte, with 10 ≤ E1 ≤ 30, preferably 10 ≤ E1 ≤ 20. For example, the value of E1 can be 10, 15, 20, 25, 30, or a range of any two of these values. By adjusting the value of E1 within the above range, fluoroethylene carbonate can participate more fully in the formation of the negative electrode SEI film, constructing a film layer with a stable structure and good lithium-ion conductivity, which is beneficial to improving the film quality on the negative electrode side and thus improving the high-temperature cycle performance of the secondary battery.

[0039] In some embodiments of this application, the mass percentage of 2,2-difluoroethyl acetate is E2% based on the mass of the electrolyte, with 20 ≤ E2 ≤ 50, preferably 20 ≤ E2 ≤ 40. For example, the value of E2 can be 20, 25, 30, 35, 40, 45, 50, or a range of any two of these values. By adjusting the value of E2 within the above range, on the one hand, 2,2-difluoroethyl acetate can appropriately increase the dielectric constant of the electrolyte, enhance the electrolyte's ability to dissolve lithium salts, and reduce the electrolyte's viscosity, which is beneficial for improving the electrolyte's ion conductivity and thus improving the low-temperature rate discharge performance of the secondary battery; on the other hand, 2,2-difluoroethyl acetate can also form a dense negative electrode SEI film with good lithium-ion conductivity, which is beneficial for improving the film quality on the negative electrode side and thus improving the high-temperature cycle performance of the secondary battery.

[0040] In some embodiments of this application, the silicon-containing material is a silicon-carbon material, and the mass percentage of silicon element is W2% based on the mass of the silicon-carbon material, with 50 ≤ W2 ≤ 85. For example, the value of W2 can be 50, 55, 60, 65, 70, 75, 80, 85, or a range of any two of these values. By adjusting the value of W2 within the above range, it is not only beneficial to utilize the high specific capacity of silicon, thereby improving the energy density of the secondary battery, but also to control the volume expansion and conductivity of the negative electrode at a reasonable level, reducing SEI film rupture caused by drastic volume changes, thereby improving the high-temperature cycle performance and low-temperature rate discharge performance of the secondary battery. In some embodiments of this application, the mass percentage of carbon element can be 15% to 50% based on the mass of the silicon-carbon material.

[0041] This application does not impose any particular restrictions on the method of controlling the mass percentage of silicon in silicon-containing materials, as long as the purpose of this application can be achieved. For example, silicon-containing materials with different silicon contents can be obtained by purchase.

[0042] In some embodiments of this application, the negative electrode active material further includes graphite, and the mass percentage of silicon-containing material is W3% based on the mass of the negative electrode active material, with 50 ≤ W3 ≤ 90. For example, the value of W3 can be 50, 55, 60, 65, 70, 75, 80, 85, 90, or a range of any two of these values. By adjusting the value of W3 within the above range, the characteristics of silicon-containing material and graphite can be balanced. This allows for both improved energy density of the secondary battery by utilizing the silicon-containing material and enhanced low-temperature rate discharge performance and high-temperature cycle performance by leveraging the excellent conductivity and structural stability of graphite. Furthermore, it can reduce costs. In some embodiments of this application, the mass percentage of graphite can be from 10% to 50% based on the mass of the negative electrode active material.

[0043] In some embodiments of this application, the silicon-containing material is a silicon-carbon material, and the particle size Dv50 of the silicon-carbon material satisfies: 4μm ≤ Dv50 ≤ 8μm. For example, the value of Dv50 can be 4μm, 5μm, 6μm, 8μm, or a range of any two of these values. By controlling the particle size Dv50 of the silicon-carbon material within the above range, the silicon-carbon material can be more uniformly dispersed in graphite to form a continuous conductive network, which is beneficial to improving the low-temperature rate discharge performance of the secondary battery.

[0044] In some embodiments of this application, the silicon-containing material is a silicon-carbon material, and the particle size Dv99 of the silicon-carbon material satisfies: 16μm ≤ Dv99 ≤ 25μm. For example, the value of Dv99 can be 16μm, 18μm, 20μm, 22μm, 25μm, or a range of any two of these values. By controlling the particle size Dv99 of the silicon-carbon material within the above range, the number of ultra-large particles can be controlled, avoiding excessive volume expansion of large silicon-carbon material during lithium intercalation, which is beneficial to improving the high-temperature cycle performance of the secondary battery.

[0045] In some embodiments of this application, the silicon-containing material is a silicon-carbon material, and the particle size Dn10 of the silicon-carbon material satisfies the following condition: 0.5 μm ≤ Dn10 ≤ 3 μm. For example, the value of Dn10 can be 0.5 μm, 1 μm, 2 μm, 3 μm, or a range of any two of these values. By controlling the particle size Dn10 of the silicon-carbon material within the above range, the proportion of ultrafine particles can be limited, particle agglomeration can be prevented, and the formation of a continuous conductive network can be facilitated, thereby improving the low-temperature rate discharge performance of the secondary battery.

[0046] In some embodiments of this application, the silicon-containing material is a silicon-carbon material, and the particle size Dv50 of the silicon-carbon material satisfies: 4μm≤Dv50≤8μm; Dv99 satisfies: 16μm≤Dv99≤25μm. By controlling the particle size Dv50 and Dv99 of the silicon-carbon material within the above ranges, it is beneficial to achieve uniform dispersion of the silicon-carbon material in graphite, and the number of ultra-large particles can be controlled, avoiding excessive volume expansion of large silicon-carbon material during lithium intercalation. This is beneficial to improving the low-temperature rate discharge performance and high-temperature cycle performance of the secondary battery.

[0047] In some embodiments of this application, the silicon-containing material is a silicon-carbon material, and the particle size Dv50 of the silicon-carbon material satisfies: 4μm≤Dv50≤8μm; Dn10 satisfies: 0.5μm≤Dn10≤3μm. By controlling the particle size Dv50 and Dn10 of the silicon-carbon material within the above ranges, not only can the silicon-carbon material be more uniformly dispersed in graphite, but the proportion of ultrafine particles can also be limited, preventing particle agglomeration, which is conducive to the formation of a continuous conductive network, thereby improving the low-temperature rate discharge performance of the secondary battery.

[0048] In some embodiments of this application, the silicon-containing material is a silicon-carbon material, and the particle size Dv99 of the silicon-carbon material satisfies: 16μm≤Dv99≤25μm; Dn10 satisfies: 0.5μm≤Dn10≤3μm. By controlling the particle size Dv99 and Dn10 of the silicon-carbon material within the above ranges, the number of ultra-large particles can be controlled, avoiding excessive volume expansion during lithium intercalation of large silicon-carbon materials, and the proportion of ultra-fine particles can be limited to prevent particle agglomeration, thereby improving the low-temperature rate discharge performance and high-temperature cycle performance of the secondary battery.

[0049] In some embodiments of this application, the silicon-containing material is a silicon-carbon material, and the particle size Dv50 of the silicon-carbon material satisfies: 4μm≤Dv50≤8μm; Dv99 satisfies: 16μm≤Dv99≤25μm; and Dn10 satisfies: 0.5μm≤Dn10≤3μm. By controlling the particle sizes Dv50, Dv99, and Dn10 of the silicon-carbon material within the above ranges, the silicon-carbon material can be uniformly dispersed in graphite to form a continuous conductive network, which is beneficial to improving the low-temperature rate discharge performance of the secondary battery; moreover, it can avoid excessive volume expansion when large silicon-carbon material particles are intercalated with lithium, which is beneficial to improving the high-temperature cycle performance of the secondary battery.

[0050] This application does not impose any particular limitation on the method of controlling the particle sizes Dv50, Dv99, and Dn10 of silicon carbide materials, as long as the purpose of this application can be achieved. For example, silicon carbide materials of different particle sizes can be purchased, and their particle sizes can be measured using a Malvern particle size analyzer to select the silicon carbide material with the desired particle size. For example, the particle sizes Dv50, Dv99, and Dn10 of silicon carbide materials can be controlled by grinding them. For instance, the particle sizes Dv50, Dv99, and Dn10 of silicon carbide materials can be controlled by adjusting the grinding time. For example, when other conditions remain unchanged, extending the grinding time decreases the particle sizes Dv50, Dv99, and Dn10 of silicon carbide materials; or, shortening the grinding time increases the particle sizes Dv50, Dv99, and Dn10 of silicon carbide materials.

[0051] In this application, Dv50 represents the particle size that reaches 50% of the volumetric cumulative size in the particle size distribution of the material, starting from the smallest particle size; Dv99 represents the particle size that reaches 99% of the volumetric cumulative size in the particle size distribution of the material, starting from the smallest particle size; and Dn10 represents the particle size that reaches 10% of the number of particles in the particle size distribution of the material, starting from the smallest particle size.

[0052] This application does not impose any particular restrictions on the negative electrode current collector, as long as it can achieve the purpose of this application. For example, it may include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, or composite current collector. For example, the composite current collector may be lithium copper composite current collector, carbon copper composite current collector, nickel copper composite current collector, titanium copper composite current collector, etc.

[0053] The negative electrode material layer of this application also includes a negative electrode binder and a negative electrode conductive agent. This application does not impose any particular limitations on the negative electrode binder and negative electrode conductive agent in the negative electrode material layer, as long as they achieve the purpose of this application. For example, the negative electrode binder may include, but is not limited to, at least one of polyacrylic acid, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyvinyl alcohol, carboxymethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polyimide, polyamide-imide, styrene-butadiene rubber, or polyvinylidene fluoride. The negative electrode conductive agent may include, but is not limited to, at least one of conductive carbon black, carbon nanotubes (CNTs), carbon fibers, flake graphite, graphene, metallic materials, or conductive polymers. The conductive carbon black may include, but is not limited to, at least one of acetylene black, Ketjen black, or Super P. The aforementioned carbon nanotubes may include, but are not limited to, single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The aforementioned carbon fibers may include, but are not limited to, vapor-grown carbon fibers (VGCF) and / or carbon nanofibers. The aforementioned metallic materials may include, but are not limited to, metal powders and / or metal fibers; specifically, the metal may include, but is not limited to, at least one of copper, nickel, aluminum, or silver. The aforementioned conductive polymer may include, but is not limited to, at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene, or polypyrrole. This application does not impose any particular limitation on the weight ratio of the negative electrode active material, negative electrode binder, and negative electrode conductive agent in the negative electrode material layer. Those skilled in the art can select these ratios according to actual needs, as long as the purpose of this application is achieved. For example, based on the mass of the negative electrode material layer, the mass percentage of the negative electrode active material may be 92% to 98%, the mass percentage of the negative electrode conductive agent may be 0.5% to 1.5%, and the mass percentage of the negative electrode binder may be 0.8% to 7%.

[0054] This application does not impose any particular limitation on the thickness of the negative electrode current collector, as long as it achieves the purpose of this application. For example, the thickness of the negative electrode current collector can be from 4 μm to 15 μm. This application also does not impose any particular limitation on the thickness of the negative electrode material layer, as long as it achieves the purpose of this application. For example, the thickness of the single-sided negative electrode material layer can be from 30 μm to 120 μm.

[0055] This application does not impose any particular restrictions on the positive electrode current collector, as long as it can achieve the purpose of this application. For example, it may include aluminum foil, aluminum alloy foil, or composite current collector (such as aluminum-carbon composite current collector).

[0056] The positive electrode material layer of this application further includes a positive electrode binder and a positive electrode conductive agent. This application does not particularly limit the types of positive electrode conductive agents and positive electrode binders, as long as they achieve the purpose of this application. For example, they can be at least one of the aforementioned negative electrode conductive agents and negative electrode binders. This application does not particularly limit the weight ratio of the positive electrode conductive agent and the positive electrode binder in the positive electrode material layer; those skilled in the art can choose according to actual needs, as long as the purpose of this application is achieved. For example, based on the mass of the positive electrode material layer, the mass percentage content of the positive electrode conductive agent can be 1% to 2%, and the mass percentage content of the positive electrode binder can be 1% to 3%.

[0057] This application does not impose any particular limitations on the thickness of the positive electrode current collector and the positive electrode material layer, as long as the purpose of this application can be achieved. For example, the thickness of the positive electrode current collector can be 5 μm to 20 μm, and the thickness of the positive electrode material layer can be 30 μm to 120 μm.

[0058] The electrolyte of this application also includes lithium salts and non-aqueous solvents. The lithium salt may include, but is not limited to, at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, Li2SiF6, lithium bis(oxalato)borate (LiBOB), or lithium difluoroborate. This application does not impose any particular limitation on the content of lithium salts in the electrolyte, as long as the purpose of this application is achieved. For example, based on the mass of the electrolyte, the mass percentage of lithium salts may be 8% to 15%.

[0059] This application does not impose any particular restrictions on non-aqueous solvents, as long as they can achieve the purpose of this application. For example, non-aqueous solvents may include, but are not limited to, at least one of carbonate compounds, carboxylic acid ester compounds, ether compounds, or other organic solvents.

[0060] The aforementioned carbonate compounds may include, but are not limited to, at least one of chain carbonate compounds, cyclic carbonate compounds, or fluorocarbonate compounds. The aforementioned chain carbonate compounds may include, but are not limited to, at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), or methyl ethyl carbonate (MEC). The aforementioned cyclic carbonate compounds may include, but are not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), butyl carbonate (BC), or vinyl ethylene carbonate (VEC). Fluorocarbonate compounds may include, but are not limited to, at least one of 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, or trifluoromethylethylene carbonate. The aforementioned carboxylic acid ester compounds may include, but are not limited to, at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanolactone, valproic acid lactone, or caprolactone. The aforementioned ether compounds may include, but are not limited to, at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran, or tetrahydrofuran. Other organic solvents may include, but are not limited to, at least one of dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolium ketone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, or trioctyl phosphate. This application does not impose any particular limitation on the content of non-aqueous solvents in the electrolyte, as long as the purpose of this application is achieved. For example, based on the mass of the electrolyte, the mass percentage of non-aqueous solvents may be 12% to 55%.

[0061] In this application, the secondary battery also includes a separator. This application does not impose any particular limitation on the separator, as long as it achieves the purpose of this application. For example, the separator material may include, but is not limited to, at least one of polyethylene (PE), polyolefins (PO) primarily composed of polypropylene (PP), polyester (e.g., polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex, or aramid. The separator type may include at least one of woven membrane, nonwoven membrane, microporous membrane, composite membrane, rolled membrane, or spun membrane.

[0062] In this application, the separator may include a substrate layer and a surface treatment layer. The substrate layer may be a nonwoven fabric, membrane, or composite membrane with a porous structure, and the material of the substrate layer may include at least one of polyethylene, polypropylene, polyethylene terephthalate, or polyimide. Optionally, a polypropylene porous membrane, a polyethylene porous membrane, a polypropylene nonwoven fabric, a polyethylene nonwoven fabric, or a polypropylene-polyethylene-polypropylene porous composite membrane may be used. Optionally, a surface treatment layer is provided on at least one surface of the substrate layer. The surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by mixing polymers and inorganic materials. The inorganic layer includes inorganic particles and a binder. This application does not have any particular limitation on the inorganic particles. For example, the inorganic particles may include at least one of alumina, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, or barium sulfate. This application does not have any particular limitation on the binder. For example, the binder may be at least one of the above-mentioned negative electrode binders. The polymer layer includes a polymer, the polymer material of which includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, or polyvinylidene fluoride or poly(vinylidene fluoride-hexafluoropropylene).

[0063] In this application, there is no particular limitation on the thickness of the diaphragm, as long as it can achieve the purpose of this application. For example, the thickness of the diaphragm can be from 3 μm to 30 μm.

[0064] The secondary battery also includes a casing for housing the positive electrode, separator, negative electrode, and electrolyte, as well as other components known in the field of secondary batteries. This application does not limit the scope of these other components. This application does not impose any particular limitation on the casing; it can be a casing known in the art, as long as it achieves the purpose of this application. For example, the casing can be a rigid casing or a flexible casing. The material of the rigid casing can be metal; this application does not limit the type of metal and can use known metal rigid casings, as long as they achieve the purpose of this application. The flexible casing can be a metal plastic film, such as aluminum-plastic film, steel-plastic film, etc.

[0065] This application does not impose any particular limitation on the type of secondary battery, which may include any device in which an electrochemical reaction occurs. In this application, the secondary battery may include, but is not limited to: lithium metal secondary batteries, lithium-ion secondary batteries (lithium-ion batteries), lithium polymer secondary batteries, or lithium-ion polymer secondary batteries, etc.

[0066] The fabrication process of the secondary battery described in this application is well known to those skilled in the art, and this application does not impose any particular limitations. For example, the fabrication process of the secondary battery may include, but is not limited to, the following steps: stacking the positive electrode, separator, and negative electrode in sequence, and performing operations such as winding and folding as needed to obtain a wound electrode assembly; placing the electrode assembly into a housing; injecting electrolyte into the housing and sealing it to obtain the secondary battery. Alternatively, stacking the positive electrode, separator, and negative electrode in sequence, and then fixing the four corners of the entire stacked structure with tape to obtain a stacked electrode assembly; placing the electrode assembly into a housing; injecting electrolyte into the housing and sealing it to obtain the secondary battery. In addition, overcurrent protection elements, conductive plates, etc., may be placed in the housing as needed to prevent pressure rise and overcharging / discharging inside the secondary battery.

[0067] A second aspect of this application provides an electronic device comprising a secondary battery as described in any of the foregoing embodiments.

[0068] Therefore, the electronic device provided in this application has good performance.

[0069] This application does not specifically limit the type of electronic device; it can be any electronic device known in the prior art. In some embodiments of this application, the electronic device may include, but is not limited to, laptops, pen input computers, mobile computers, e-book players, portable telephones, portable fax machines, portable copiers, portable printers, stereo headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini CDs, transceivers, electronic notebooks, calculators, memory cards, portable recorders, radios, backup power supplies, motors, automobiles, motorcycles, electric bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries, and lithium-ion capacitors, etc.

[0070] Example

[0071] The embodiments and comparative examples provided below illustrate the implementation of this application in more detail. Various tests and evaluations were conducted according to the methods described below. Furthermore, unless otherwise specified, "parts" and "%" are quality standards.

[0072] Test methods and equipment:

[0073] Test of the mass percentage of silicon in the negative electrode material layer:

[0074] The lithium-ion batteries in each embodiment or comparative example were discharged at a constant current of 0.5C to the discharge cutoff voltage of 3.0V, and then disassembled to obtain the negative electrode sheet. The negative electrode sheet was then immersed in dimethyl carbonate (DMC) at room temperature for 30 minutes and air-dried to obtain the dried negative electrode sheet. Small discs with a diameter of 14mm were randomly selected from the negative electrode sheet, and surface energy dispersive spectroscopy (EDS) was performed on the negative electrode material layer on the small discs. The test area was magnified 3000 times, and EDS was performed on the entire area after magnification 3000 times to obtain the types and mass percentages of elements in the negative electrode material layer.

[0075] The discharge cutoff voltage is based on the markings on the battery. In this embodiment, the discharge cutoff voltage is 3.0V and the charging limit voltage is 4.5V, which will not be repeated hereafter.

[0076] Test of the mass percentage of silicon in silicon-containing materials:

[0077] The lithium-ion batteries in each embodiment or comparative example were discharged at a constant current of 0.5C to the discharge cutoff voltage of 3.0V, and then disassembled to obtain the negative electrode sheet. The negative electrode sheet was soaked in dimethyl carbonate (DMC) for 20 minutes, and then rinsed with DMC and acetone sequentially. The negative electrode sheet was then placed in an oven and baked at 80°C for 12 hours to obtain a dried negative electrode sheet. The negative electrode material layer on the negative electrode sheet was scraped off with a blade, and a mg sample of the negative electrode material layer powder was taken and scanned using energy-dispersive X-ray spectroscopy (EDS). Elemental analysis was performed on individual silicon-containing material particles to obtain the mass percentage (W2) of silicon in the silicon-containing material particles.

[0078] Particle size testing of silicon-containing materials: Dv50, Dv99, Dn10:

[0079] The lithium-ion batteries in each embodiment or comparative example were discharged at a constant current of 0.5C to a discharge cutoff voltage of 3.0V, and then disassembled to obtain the negative electrode sheet. The negative electrode sheet was then immersed in DMC at room temperature for 30 minutes and air-dried to obtain the dried negative electrode sheet. The negative electrode material layer on the negative electrode sheet was scraped off with a blade, and then the silicon-containing material was obtained by differential centrifugation. Differential centrifugation is a method of separation that utilizes the difference in sedimentation velocity of different particles in a centrifugal field. In this method, particles with higher density will settle first, while particles with lower density require higher centrifugal force and longer time to settle.

[0080] The specific steps are as follows: The scraped negative electrode material layer powder is made into a suspension. Under the action of gravity or centrifugal force, different particles settle. Based on the settling velocity of different particles, the silicon-containing material, graphite, negative electrode binder, and negative electrode conductive agent in the negative electrode material layer can be separated. The above suspension preparation method is as follows: 100g of negative electrode material layer powder is added to 1.0L of deionized water. Under ice bath conditions, the negative electrode material is broken down using a homogenizer to form a uniform suspension of 0.1g / mL.

[0081] Elemental analysis was performed on the different substances obtained above. Those containing silicon were identified as silicon-containing materials. The particle sizes Dv50, Dv99, and Dn10 of the silicon-containing materials were determined using a laser particle size analyzer (such as MalvernMaster Size 3000) in accordance with the national standard GB / T 19077-2016 (Laser Diffraction Method for Particle Size Distribution).

[0082] Particle size testing of lithium cobalt oxide particles:

[0083] The lithium-ion batteries in each embodiment or comparative example were disassembled after being discharged at a constant current of 0.5C to the discharge cutoff voltage of 3.0V to obtain the positive electrode sheet. The positive electrode sheet was then longitudinally cut along the thickness direction using plasma and polished using argon ion polishing technology to obtain a flat cross-section. SEM images were then taken at a magnification of 50,000 using a scanning electron microscope (SEM, model OXFORD·EDS) to observe the lithium cobalt oxide particles. Using image analysis software, 30 lithium cobalt oxide particles were randomly selected from the SEM images, and the area of ​​each particle was calculated. Then, assuming the lithium cobalt oxide particles are spherical, their particle diameter D was calculated using the following formula: D = 2 × (S1 / π). 1 / 2 Where S1 is the area of ​​the lithium cobalt oxide particle; and the average particle size of the 30 lithium cobalt oxide particles is the average particle size of the lithium cobalt oxide particles.

[0084] Content testing of fluoroethylene carbonate and 2,2-difluoroethyl acetate:

[0085] The lithium-ion batteries in each embodiment or comparative example were discharged at a constant current of 0.5C to the discharge cutoff voltage of 3.0V. After that, the outer packaging of the lithium-ion batteries was cut open and removed, the electrode assembly was centrifuged, and the electrolyte after centrifugation was tested by gas chromatography-mass spectrometry (GC-MS) in a vacuum glove box filled with nitrogen to obtain the contents of fluoroethylene carbonate and 2,2-difluoroethyl acetate.

[0086] High-temperature cycling performance test:

[0087] Under 45°C conditions, the lithium-ion batteries in each embodiment or comparative example were charged at a constant current of 2C to the charging limit voltage of 4.5V, then charged at a constant voltage of 4.5V to a current of 0.05C, and then discharged at a constant current of 0.5C to the discharge cutoff voltage of 3.0V. This was recorded as the discharge capacity of the first cycle. The lithium-ion batteries were subjected to 200 cycles under the above conditions, and the discharge capacity after 200 cycles was recorded. The high-temperature cycling performance of the lithium-ion battery was characterized by the 45°C cycle capacity retention rate; the higher the 45°C cycle capacity retention rate, the better the high-temperature cycling performance of the lithium-ion battery.

[0088] 45℃ cycle capacity retention rate = (discharge capacity after 200 cycles / discharge capacity of the first cycle) × 100%.

[0089] Low-temperature rate discharge performance test:

[0090] At 25°C, the lithium-ion batteries in each embodiment or comparative example were charged at a constant current of 0.2C to the charging limit voltage of 4.5V, then charged at a constant voltage of 4.5V to a current of 0.05C. After resting for 5 minutes, they were discharged at a constant current of 0.2C to the discharge cutoff voltage of 3.0V, and then rested for 5 minutes. The capacity of the above discharge process was recorded as C1. The temperature was adjusted to -20°C, and the same charging and discharging steps were repeated to obtain the discharge capacity C2. The low-temperature rate discharge capacity retention rate C (%) = C2 / C1 × 100%. The higher the low-temperature rate discharge capacity retention rate, the better the low-temperature rate discharge performance of the lithium-ion battery.

[0091] Energy density test:

[0092] The voltage range indicated on the outer packaging of the lithium-ion battery shall prevail. For example, when the voltage range indicated on the outer packaging of the lithium-ion battery is 3.0V to 4.5V, the charging limit voltage is 4.5V and the discharge cut-off voltage is 3.0V.

[0093] The specific test steps are as follows: Under 25℃ conditions, the lithium-ion batteries in each embodiment or comparative example are charged at a constant current of 0.2C to the charging limit voltage of 4.5V, then charged at a constant voltage of 4.5V to a current of 0.05C. After standing for 5 minutes, they are discharged at a constant current of 0.2C to the discharge cutoff voltage of 3.0V, and then stood for 5 minutes. The energy of the above discharge process is recorded as the discharge energy E. Calculate the volume V (mm²) of the lithium-ion battery. 3 = Length × Width × Height. The energy density of a lithium-ion battery is calculated using the following formula: Energy density (Wh / L) = E / V × 10 6 .

[0094] Example 1-1

[0095] <Preparation of the positive electrode>

[0096] Lithium cobalt oxide (LiCoO2), a positive electrode active material, polyvinylidene fluoride (PVDF), a positive electrode binder, and single-walled carbon nanotubes, a positive electrode conductive agent, were mixed in a weight ratio of 97:2:1. N-methylpyrrolidone (NMP) was added as a solvent, and the mixture was stirred until homogeneous to obtain a positive electrode slurry with a solid content of 75 wt%. The positive electrode slurry was uniformly coated onto one surface of a 10 μm thick aluminum foil used as a positive electrode current collector, and dried at 120 °C for 1 hour to obtain a positive electrode sheet with a single-sided coating of the positive electrode material layer. The coating weight of the positive electrode material layer was 320 mg / cm³. 2 The above steps are then repeated on the other surface of the aluminum foil to obtain a positive electrode sheet with a double-sided coating of positive electrode material. After drying under vacuum at 120℃ for 1 hour, the sheet is cold-pressed, cut, and slit to obtain a positive electrode sheet with dimensions of 74mm × 867mm. The thickness of the single-sided positive electrode material layer is 42μm.

[0097] <Preparation of Negative Electrode Sheets>

[0098] A mixture of silicon-carbon anode active material, artificial graphite anode active material, polyacrylic acid anode binder, and single-walled carbon nanotubes anode conductive agent in a weight ratio of 67.9:29.1:2.5:0.5 was prepared by adding deionized water as a solvent to form a slurry with a solid content of 45 wt%. The slurry was then stirred uniformly in a vacuum mixer to obtain the anode slurry. Based on the mass of the silicon-carbon material, the mass percentage of silicon (W2) was 67%, and the mass percentage of carbon was 33%. The anode slurry was uniformly coated onto one surface of a 6 μm thick copper foil anode current collector and dried at 60°C for 1 hour to obtain a single-sided coated anode electrode sheet with a coating weight of 80 mg / cm³. 2 Then, the above steps are repeated on the other surface of the copper foil to obtain a negative electrode sheet with a double-sided coating of negative electrode material. After drying at 120℃ under vacuum for 1 hour, it is then cold-pressed, cut, and slit to obtain a negative electrode sheet with dimensions of 78mm × 875mm for later use. The thickness of the single-sided negative electrode material layer is 54.5μm.

[0099] <Preparation of Electrolyte>

[0100] In an environment with a water content of less than 10 ppm, dimethyl carbonate, diethyl carbonate, and ethylene carbonate are mixed in a weight ratio of 1:1:1 to obtain an organic solvent. Subsequently, fluoroethylene carbonate (FEC), 2,2-difluoroethyl acetate, and lithium salt LiPF6 are added sequentially and mixed thoroughly to obtain the electrolyte. Based on the mass of the electrolyte, the mass percentages of FEC, 2,2-difluoroethyl acetate, and lithium salt are 12.5%, with the remainder being the organic solvent.

[0101] <Preparation of the diaphragm>

[0102] A porous polyethylene film with a thickness of 7μm (provided by Celgard) was used as the separator.

[0103] <Preparation of Lithium-ion Batteries>

[0104] The prepared positive electrode, separator, negative electrode, and separator are stacked in sequence, with the separator positioned between the positive and negative electrode to act as a separator. The electrode assembly is then wound to obtain the electrode assembly. After welding the tabs, the electrode assembly is placed in an aluminum-plastic film packaging bag and dehydrated at 80°C. The electrolyte prepared above is then injected, and the battery undergoes vacuum sealing, settling, formation, degassing, and edge trimming processes to obtain a lithium-ion battery.

[0105] Examples 1-2 to 1-25

[0106] Except for adjusting the relevant preparation parameters according to Table 1, the preparation method is the same as in Example 1-1.

[0107] Examples 2-1 to 2-4

[0108] Except for adjusting the relevant preparation parameters according to Table 2, the preparation methods are the same as those in Examples 1-1.

[0109] Comparative Examples 1 to 9

[0110] Except for adjusting the relevant preparation parameters according to Table 1, the preparation method is the same as in Example 1-1.

[0111] The preparation parameters and electrical performance parameters of each embodiment and comparative example are shown in Tables 1 and 2.

[0112] Table 1

[0113] Examples 1-1 to 1-25 and Comparative Examples 1 to 9 show that when the mass percentage of silicon in the negative electrode material layer, the particle size of lithium cobalt oxide particles in the positive electrode material layer, and the mass percentage of fluorine-containing compounds in the electrolyte are within the scope of this application, the prepared lithium-ion batteries exhibit high energy density, high low-temperature rate discharge capacity retention, and 45°C cycle capacity retention. This indicates that lithium-ion batteries possess both high energy density and good low-temperature rate discharge performance and high-temperature cycle performance. In Comparative Examples 1 to 9, the mass percentage of silicon in the negative electrode material layer and / or the particle size of lithium cobalt oxide particles in the positive electrode material layer and / or the mass percentage of fluorine-containing compounds in the electrolyte are outside the scope of this application. The prepared lithium-ion batteries exhibit lower energy density and / or lower low-temperature rate discharge capacity retention and / or lower 45°C cycle capacity retention. This indicates that lithium-ion batteries cannot achieve a balance between high energy density, good low-temperature rate discharge performance, and high-temperature cycle performance.

[0114] The mass percentage of silicon-containing material in the negative electrode material layer affects the energy density, low-temperature rate discharge performance, and high-temperature cycle performance of lithium-ion batteries. As can be seen from Examples 1-1 to 1-5 and Comparative Example 1, by controlling the mass percentage of silicon-containing material within the scope of this application, lithium-ion batteries exhibit higher energy density, higher low-temperature rate discharge capacity retention, and higher 45°C cycle capacity retention. This indicates that lithium-ion batteries possess both high energy density and good low-temperature rate discharge performance and high-temperature cycle performance.

[0115] The mass percentage of silicon in silicon-containing materials affects the energy density, low-temperature rate discharge performance, and high-temperature cycle performance of lithium-ion batteries. As can be seen from Examples 1-1, 1-6 to 1-9, by controlling the mass percentage of silicon in the silicon-containing materials within the scope of this application, lithium-ion batteries exhibit higher energy density, higher low-temperature rate discharge capacity retention, and higher 45°C cycle capacity retention. This indicates that lithium-ion batteries possess both high energy density and good low-temperature rate discharge performance and high-temperature cycle performance.

[0116] The mass percentage of silicon in the negative electrode material layer affects the energy density, low-temperature rate discharge performance, and high-temperature cycle performance of lithium-ion batteries. As can be seen from Examples 1-1 to 1-10 and Comparative Example 1, by controlling the mass percentage of silicon in the negative electrode material layer within the scope of this application, lithium-ion batteries exhibit higher energy density, higher low-temperature rate discharge capacity retention, and higher 45°C cycle capacity retention. This demonstrates that lithium-ion batteries possess both high energy density and good low-temperature rate discharge performance and high-temperature cycle performance.

[0117] The particle size of lithium cobalt oxide particles in the cathode material layer affects the low-temperature rate discharge performance and high-temperature cycle performance of lithium-ion batteries. As can be seen from Examples 1-1, 1-11 to 1-14, and Comparative Examples 2 and 3, by controlling the particle size of lithium cobalt oxide particles within the scope of this application, lithium-ion batteries exhibit higher energy density, higher low-temperature rate discharge capacity retention, and higher 45°C cycle capacity retention. This demonstrates that lithium-ion batteries possess both high energy density and good low-temperature rate discharge performance and high-temperature cycle performance.

[0118] The mass percentage of 2,2-difluoroethyl acetate affects the low-temperature rate discharge performance and high-temperature cycle performance of lithium-ion batteries. As can be seen from Examples 1-1, 1-16 to 1-20, and Comparative Examples 4 and 5, by adjusting the mass percentage of 2,2-difluoroethyl acetate within the scope of this application, lithium-ion batteries exhibit higher energy density, higher low-temperature rate discharge capacity retention, and higher 45°C cycle capacity retention. This demonstrates that lithium-ion batteries possess both high energy density and good low-temperature rate discharge performance and high-temperature cycle performance.

[0119] The mass percentage of fluoroethylene carbonate affects the high-temperature cycling performance of lithium-ion batteries. As can be seen from Examples 1-1, 1-21 to 1-25, by adjusting the mass percentage of fluoroethylene carbonate within the scope of this application, lithium-ion batteries exhibit higher energy density, higher low-temperature rate discharge capacity retention, and higher 45°C cycle capacity retention. This demonstrates that lithium-ion batteries possess both high energy density and good low-temperature rate discharge performance, as well as good high-temperature cycling performance.

[0120] The mass percentage of fluorinated compounds affects the low-temperature rate discharge performance and high-temperature cycle performance of lithium-ion batteries. As can be seen from Examples 1-1, 1-15 to 1-25, and Comparative Examples 4 and 5, by controlling the mass percentage of fluorinated compounds within the scope of this application, lithium-ion batteries exhibit higher energy density, higher low-temperature rate discharge capacity retention, and higher 45°C cycle capacity retention. This demonstrates that lithium-ion batteries possess both high energy density and good low-temperature rate discharge performance and high-temperature cycle performance.

[0121] Table 2

[0122] The particle size of silicon-carbon materials typically affects the low-temperature rate discharge performance and high-temperature cycling performance of lithium-ion batteries. As can be seen from Examples 1-1 and 2-1 to 2-4, by controlling the particle size of the silicon-carbon materials within the scope of this application, the prepared lithium-ion batteries exhibit high energy density, high low-temperature rate discharge capacity retention, and high 45°C cycle capacity retention. This demonstrates that the lithium-ion batteries possess both high energy density and good low-temperature rate discharge performance and high-temperature cycling performance.

[0123] from Figure 1 and Figure 2 As can be seen, the lithium cobalt oxide particles in Example 1-1 have smaller particle sizes and denser contact between them, while the lithium cobalt oxide particles in Comparative Example 3 have larger particle sizes and are less likely to form dense contact. Figure 3 It can be seen that silicon-carbon materials can be uniformly dispersed in graphite. From Figure 4 It can be seen that the SEI film on the surface of silicon-carbon particles after high-temperature cycling is thin and intact, with almost no additional side reaction erosion.

[0124] It should be noted that, in this document, the terms “comprising,” “including,” or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, or article that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, or article.

[0125] The various embodiments in this specification are described in a related manner. The same or similar parts between the various embodiments can be referred to each other. Each embodiment focuses on describing the differences from other embodiments.

[0126] The above description is only a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the scope of protection of this application.

Claims

1. A secondary battery comprising a negative electrode, a positive electrode, and an electrolyte, wherein the negative electrode comprises a negative current collector and a negative electrode material layer disposed on at least one surface of the negative current collector, the negative electrode material layer comprises a negative electrode active material, the negative electrode active material comprises a silicon-containing material, and the mass percentage of silicon element based on the mass of the negative electrode material layer is W1%, 25≤W1≤70; The positive electrode sheet includes a positive current collector and a positive electrode material layer disposed on at least one surface of the positive current collector. The positive electrode material layer includes lithium cobalt oxide, and the particle size of the lithium cobalt oxide particles is D μm, where 2≤D≤10. The electrolyte comprises a fluorinated compound, which includes at least one of fluoroethylene carbonate or 2,2-difluoroethyl acetate; the mass percentage of the fluorinated compound is E% based on the mass of the electrolyte, with a mass percentage of 30 ≤ E ≤ 80.

2. The secondary battery according to claim 1, wherein, 32≤W1≤58。 3. The secondary battery according to claim 1, wherein, 4≤D≤8。 4. The secondary battery according to claim 1, wherein, Based on the mass of the electrolyte, the mass percentage of fluoroethylene carbonate is E1%, where 10 ≤ E1 ≤ 30.

5. The secondary battery according to claim 4, wherein, 10≤E1≤20。 6. The secondary battery according to claim 1, wherein, Based on the mass of the electrolyte, the mass percentage of 2,2-difluoroethyl acetic acid is E2%, where 20 ≤ E2 ≤ 50.

7. The secondary battery according to claim 6, wherein, 20≤E2≤40。 8. The secondary battery according to claim 1, wherein, The silicon-containing material is a silicon-carbon material, and based on the mass of the silicon-carbon material, the mass percentage of silicon element is W2%, 50≤W2≤85%.

9. The secondary battery according to claim 1, wherein, The negative electrode active material also includes graphite, and based on the mass of the negative electrode active material, the mass percentage of the silicon-containing material is W3%, 50≤W3≤90.

10. The secondary battery according to claim 8, wherein it satisfies at least one of the following characteristics: (1) The particle size Dv50 of the silicon carbide material satisfies: 4μm≤Dv50≤8μm; (2) The particle size Dv99 of the silicon carbide material satisfies: 16μm≤Dv99≤25μm; (3) The particle size Dn10 of the silicon carbide material satisfies: 0.5μm≤Dn10≤3μm.

11. An electronic device comprising a secondary battery as described in any one of claims 1 to 10.